Exploration of hydrothermal alteration and monitoring of thermal activity using multi-source satellite images: A case study of the recently active Kirishima volcano complex on Kyushu Island, Japan. (May 2019) - Mia, Md. Bodruddoza; Fujimitsu, Yasuhiro; Nishijima, Jun
Highlights: Most active thermal area is identified using alteration and thermal anomaly. Maximum LST values declined from first to third eruption period. Highest RHF and peak of RHL reduced during the study period. Shinmoedake crater was more intense thermal activity than Ohnamiike crater. The intensity of unrest thermal activity decreased overall from the study area. Abstract: Three major successive plinian or subplinian eruptions, following a long dormant period, occurred in January 2011, September 2017, and March 2018 within the Kirishima volcano complex on Kyushu Island, Japan. Herein, we applied a Landsat 8 image to explore the most active hydrothermal altered area of the Kirishima volcano complex, and nine sets of nighttime ASTER thermal infrared data to explore changes of heat loss to the thermally active area of the Shinmoedake and Ohnamiike craters within this volcanic complex from 2009 to 2018. Color composite, band ratio, principal component analysis, and Crosta techniques were used to map hydrothermal alteration. Meanwhile, the normalized difference vegetation index threshold method for emissivity retrieval, the split-window algorithm for land surface temperature (LST), and the Stefan–Boltzmann equation were used to derive the radiative heat flux (RHF) for the study area. Total radiative heat loss (RHL) in megawatts was calculated by adding pixels positive RHF (W/m 2 ) values after multiplying with the pixel area. Using these data, the spatial distribution of altered mineral zones was mapped for the Kirishima volcano complex. We estimated that the maximum LSTs above ambient values were about 24 °C, 12 °C, and 12 °C, immediately following the 2011, 2017 and 2018 eruptions. Highest pixel RHFs of 136 W/m 2, 75 W/m 2, and 61 W/m 2 were also measured just after these eruptions, on 15 November 2011, 30 October 2017, and 8 April 2018, producing peaks in the total RHL of 233 MW, 198 MW and 101 MW, respectively. The Shinmoedake crater had more intense thermal activity than the Ohnamiike crater after both the 2011 and 2018 eruptions but had less intense activity after the 2017 eruption. The intensity of thermal unrest decreased during the study period from both craters. This study illustrates how Landsat TIRS/OLI data can be used for hydrothermal alteration as well as nighttime ASTER thermal infrared data to monitor effectively the thermal activity of active areas of the Kirishima volcano complex.